Metabolism: The road to inflammation and atherosclerosis. Issue 6 (December 2018) - Ali, Lubna; Schnitzler, Johan G.; Kroon, Jeffrey
Abstract : Purpose of review: Evidence accumulates suggesting that cellular metabolic alterations fuel and dictate the inflammatory state of cells. In this review, we provide an overview of the observed metabolic reprogramming in endothelial cells and innate immune cells upon interaction with modified lipoproteins, thereby contributing to the progression of atherosclerosis. Recent findings: Inflammatory endothelial cells at sites exposed to disturbed flow patterns show increased glycolytic activity. Atherogenic factors further enhance these metabolic changes by upregulating the mitochondrial energy production and thereby facilitating increased energy expenditure. Metabolic alterations are pivotal for monocyte and macrophage function as well. Exposure to atherogenic particles such as oxidized phospholipids lead to a regulatory metabolic pro-inflammatory phenotype, mediated via Toll-like receptor (TLR) 2 and the transcription factor erythroid 2-related factor (Nrf) 2. Translational studies highlighted the importance of metabolic alterations, as atherosclerotic plaques in the carotid arteries showed an increased glycolytic signature. Summary: Alterations in cellular metabolism play an important role in controlling and steering the inflammatory state of both endothelial cells and immune cells. Targeting glycolysis may therefore provide an interesting route to attenuate the progression of atherosclerosis.